2015
DOI: 10.1155/2015/145629
|View full text |Cite
|
Sign up to set email alerts
|

3D Gradual Material Degradation Model for Progressive Damage Analyses of Unidirectional Composite Materials

Abstract: A new 3D constitutive model for progressive damage analyses of unidirectional composite materials is presented, in which several important damage phenomena for the composite materials, such as the interfiber crack orientation, coupling of fiber failure and interfiber failure under longitudinal loads, closure effect for interfiber cracks, and longitudinal compressive behaviors under transversal constraints, have been considered comprehensively. A modified maximum stress failure criterion has been used for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 47 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…The modified maximum stress criterion ] is adopted to predict the initiation of the fiber crack and interfiber crack. The 3D gradual material degradation model [Zhao, Qin, Zhang et al (2015)] is used to define the damage evolution and the constitutive equation of the damaged materials.…”
Section: Pdmmentioning
confidence: 99%
See 3 more Smart Citations
“…The modified maximum stress criterion ] is adopted to predict the initiation of the fiber crack and interfiber crack. The 3D gradual material degradation model [Zhao, Qin, Zhang et al (2015)] is used to define the damage evolution and the constitutive equation of the damaged materials.…”
Section: Pdmmentioning
confidence: 99%
“…The material degradation model is established under a local coordinate O-1'2'3' fixed to the cracks [Zhao, Qin, Zhang et al (2015)], as shown in Fig. 8.…”
Section: Materials Degradation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of the finite element (FE) method, the continuum damage mechanics (CDM) modeling technique has proved to be an effective numerical method to investigate the failure process and ultimate strength of notched or bolted composite structures. [15][16][17][18][19][20][21] CDM assumes that material property degradation is governed by continuous damage variables. These damage variables are related to the mechanical aspects of the damage mechanism and the dissipation energy that is required for the evolution of the damage states.…”
Section: Introductionmentioning
confidence: 99%